Analisis Kemampuan Kognitif Siswa Sekolah Dasar dalam Menyelesaikan Soal Cerita Berdasarkan Teori Polya - Kusnadi, Dedi; Barumbun, Mardyanto; Hasanah, Nur Fidatul; Yusnarti, Mulya (MASALIQ, 2025)
Mathematics education is taught to students from the basic level with the aim of equipping them with various skills, such as logical, analytical, systematic, critical, and creative thinking abilities, as well as the ability to work together. One of the abilities that is measured is cognitive ability. Cognitive ability involves the thinking process in the form of generally recognizing depicted objects and can be expressed in ideas, responses, or values. This mathematics learning activity also certainly involves problems in solving mathematical story problems. The procedure for solving story problems certainly involves steps for resolution, namely by using problem-solving according to Polya's theory. This research aims to describe students' cognitive abilities in solving word problems based on Polya's theory. The research instrument used in this study was a test, confirmed through interviews. The research results show that students with moderate ability are unable to solve problems in the cognitive category of applying (calculating indicator) and creating (designing indicator) especially in the Polya stage of checking, because the checking process is not found in their answer sheets. Meanwhile, students with low ability also cannot solve problems in the applying cognitive category (calculating indicator) and creating cognitive category (designing indicator), and are unable to solve story problems using Polya's stages of planning, executing, and checking. Thus, it can be concluded that students' ability to solve LOTS and HOTS questions is still at a low level because they find it difficult to work on questions in the cognitive domains of applying and creating.